2011
DOI: 10.5798/diclemedj.0921.2011.04.0054
|View full text |Cite
|
Sign up to set email alerts
|

•The protective effects of omega-3 fatty acids on rat testicular tissue

Abstract: Objectives: In this study, the protective effect of omega-3 fatty acids on testicular tissue was aimed to investigate at biochemical levels. Materials and methods:Totally, 16 adult male Wistar rats were divided into two groups. Rats in Group I were used as control and only saline was given by intragastric gavage. Rats in Group II, 400 mg/kg dose ω-3 fatty acids were given daily by intragastric gavage. At the end of the six-week experimental period, all rats were killed by decapitation. The testicular tissue sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Fatty acid composition of the spermatozoa may be an important determinant of fertility [22]. In a study concluded that ω-3 fatty acid had favorable effects in rat testis tissue by preventing oxidative damage and increasing the level of testosterone [23]. A, C and E): Oxidative stress is the increase of the rate of cellular damage triggered by oxygen and oxygen-based oxidants known as reactive oxygen species.…”
Section: The Relationship Of Body-mass Index and Infertilitymentioning
confidence: 99%
“…Fatty acid composition of the spermatozoa may be an important determinant of fertility [22]. In a study concluded that ω-3 fatty acid had favorable effects in rat testis tissue by preventing oxidative damage and increasing the level of testosterone [23]. A, C and E): Oxidative stress is the increase of the rate of cellular damage triggered by oxygen and oxygen-based oxidants known as reactive oxygen species.…”
Section: The Relationship Of Body-mass Index and Infertilitymentioning
confidence: 99%
“…Group III: Omega-3 group: rats of this group were orally received omega-3 at a dose 400 mg/kg body weight/day 11 .…”
Section: Experimental Animal and Treatmentmentioning
confidence: 99%